2015
DOI: 10.1002/bdm.1866
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐Taking Tendencies in Prisoners and Nonprisoners: Does Gender Matter?

Abstract: Several investigations have found that prisoners are more likely than nonprisoners to engage in risky behavior, which may contribute to their propensity to commit criminal offenses. However, this research has been limited by an almost exclusive focus on male samples. Given the established link between risk taking and gender, it is thus unclear how findings on the risk-taking propensities of prisoners also hold in women. The present study uses both a self-report questionnaire (Domain-Specific Risk Taking scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…For example, Wallsten et al (2005) found that outcome sensitivity to gains (in that study referred to as ) in the BART was predictive of the number of drugs a person had tried, whether he or she had ever stolen something, and how often he or she had engaged in unprotected sex in the last year. Similarly, Wichary et al (2015) found that outcome sensitivity in the BART was positively correlated with the propensity to engage in various real-world risky activities (e.g., sky diving, smoking). In addition, a number of studies have shown that trait sensitivity to reward and/or loss as assessed by self-report measures (Carver & White, 1994) is related to risk taking in laboratory tasks (Brunborg, Johnsen, Mentzoni, Molde, & Pallesen, 2011;Demaree, DeDonno, Burns, & Erik Everhart, 2008;Penolazzi, Gremigni, & Russo, 2012) and real-life risk taking such as horse race gambling (Balodis, Thomas, & Moore, 2014).…”
Section: Convergent Validitymentioning
confidence: 86%
See 1 more Smart Citation
“…For example, Wallsten et al (2005) found that outcome sensitivity to gains (in that study referred to as ) in the BART was predictive of the number of drugs a person had tried, whether he or she had ever stolen something, and how often he or she had engaged in unprotected sex in the last year. Similarly, Wichary et al (2015) found that outcome sensitivity in the BART was positively correlated with the propensity to engage in various real-world risky activities (e.g., sky diving, smoking). In addition, a number of studies have shown that trait sensitivity to reward and/or loss as assessed by self-report measures (Carver & White, 1994) is related to risk taking in laboratory tasks (Brunborg, Johnsen, Mentzoni, Molde, & Pallesen, 2011;Demaree, DeDonno, Burns, & Erik Everhart, 2008;Penolazzi, Gremigni, & Russo, 2012) and real-life risk taking such as horse race gambling (Balodis, Thomas, & Moore, 2014).…”
Section: Convergent Validitymentioning
confidence: 86%
“…It has been suggested that these game-like tasks to evoke the affective components that also accompany naturalistic risk taking, such as the feeling of escalating tension and exhilaration when a participant pushes decisions to maximal gain against the probability of a loss (Schonberg et al, 2011). Possibly because they capture the emotional components of risk taking and appear to be more similar to naturalistic risk taking, they have been successful in differentiating healthy controls from different groups of high risk takers-for example substance abusers (Bishara et al, 2009;Bornovalova, Daughters, Hernandez, Richards, & Lejuez, 2005;Coffey, Schumacher, Baschnagel, Hawk, & Holloman, 2011;Crowley, Raymond, Mikulich-Gilbertson, Thompson, & Lejuez, 2006;Hunt, Hopko, Bare, Lejuez, & Robinson, 2005;Ledgerwood, Alessi, Phoenix, & Petry, 2009) or prisoners (Wichary, Pachur, & Li, 2015). Although we are not aware of a systematic review, relative to static lottery-type tasks without feedback, these dynamic task types seem to more often show significant correlations with self-reported "real-life" risk-taking behaviors (e.g., Aklin, Lejuez, Zvolensky, Kahler, & Gwadz, 2005;Bornovalova et al, 2009;Hunt et al, 2005;Lejuez et al, 2003;MacPherson, Magidson, Reynolds, Kahler, & Lejuez, 2010;Mishra, Lalumière, & Williams, 2010;Skeel, Pilarski, Pytlak, & Neudecker, 2008;Swogger, Walsh, Lejuez, & Kosson, 2010; for a similar argument, see Schonberg, Fox, & Poldrack 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals may also envision negative consequences of admitting to risky behaviors, motivating them to moderate their responses to comply with perceived social norms (Nederhof, ; Fisher, ). An alternative approach has been to measure behavior directly using decision‐making tasks (e.g., Bechara, Damasio, Tranel, & Damasio, ; Figner, Mackinlay, Wilkening, & Weber, ; Glöckner & Pachur, ; Hoffrage, Weber, Hertwig, & Chase, ; Holt & Laury, ; Wichary, Pachur, & Li, ). In these tasks, individuals decide on the basis of explicitly described or experienced outcomes and probabilities of the choice options.…”
mentioning
confidence: 99%
“…In order to go beyond empirical data and to understand the cognitive processes fully it is important to test mechanistic process models that try to explicitly state the underlying neurocognitive mechanisms (cf. Wichary et al, 2015b; Chuderski and Smolen, 2016). Within the domain of strategy selection in multi-attribute choice, there exists an empirical challenge described by Newell (2005) that it is impossible to distinguish, based on behavior, the accuracy of the unified and multiple strategy models described in the previous section.…”
Section: Toward a Neurocognitive Model Of Decision Strategy Selectionmentioning
confidence: 99%